Modernidad perversa: Episodios de rebelión en América Latina - Gerwer, Keren (Universidad ORT Uruguay, 2012)
This article summarizes extracts from a research project on the development of the Latin American avant-garde movement of the early twentieth century. The process was carried out by analyzing artistic and architectural episodes in Mexico, Brazil, and Argentina from this period. The goal of this research was to explore the cultural heterogeneity characteristic of Latin America, including the links with Europe and the contribution of the avant-garde to thegeneration of identity projects. Art and architecture reflected the profound changes of a new time. Avant-garde artists, modernist men, used these instruments as alternative ways of representing the conventions of the Academy. «Perverse modernity» refers to the phenomenon that is considered the major intellectual break of this period: the Latin American rebellion.